2023
DOI: 10.1111/all.15630
|View full text |Cite
|
Sign up to set email alerts
|

How does particulate air pollution affect barrier functions and inflammatory activity of lung vascular endothelium?

Abstract: Both particulate matter and gaseous components of air pollution have already been shown to increase cardiovascular mortality in numerous studies. It is, however, important to note that on their way to the bloodstream the polluting agents pass the lung barrier. Inside the alveoli, particles of approximately 0.4–1 μm are most efficiently deposited and commonly undergo phagocytosis by lung macrophages. Not only the soluble agents, but also particles fine enough to leave the alveoli enter the bloodstream in this f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 96 publications
(234 reference statements)
0
10
0
Order By: Relevance
“…8 Additionally, PM in the respiratory tract may also cross the lung epithelial barrier and consequently reach the gastrointestinal tract by blood circulation. 15 Therefore, gastrointestinal exposure is an important exposure route for PM. Several previous studies have linked PM exposure with increased risks of gastrointestinal diseases such as oesophageal cancer, IBD, and IBS, 5,7,26,27 It is reported that PM exposure could increase ROS generation, induce gastrointestinal epithelial cell death, and induce the disruption and hyperpermeability of the intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Additionally, PM in the respiratory tract may also cross the lung epithelial barrier and consequently reach the gastrointestinal tract by blood circulation. 15 Therefore, gastrointestinal exposure is an important exposure route for PM. Several previous studies have linked PM exposure with increased risks of gastrointestinal diseases such as oesophageal cancer, IBD, and IBS, 5,7,26,27 It is reported that PM exposure could increase ROS generation, induce gastrointestinal epithelial cell death, and induce the disruption and hyperpermeability of the intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it could also get into the digestive tract through contaminated food and water, mucociliary clearance of the respiratory tract, and blood circulation. [13][14][15] Based on the Integrated Science Assessment (ISA) of PM, nearly 71% of the PM deposited in the nose will consequently enter the gastrointestinal tract. 8 This indicates that, for PM, the gastrointestinal exposure pathway is important and should not be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…These risk factors impose a significant burden on the barrier function of the airway epithelium. 143 The formation of PM involves chemical reactions with compounds like sulfur dioxide and NO 2 . Numerous studies have observed that PM 2.5 and PM 10 can induce varying degrees of impairment in the nasal epithelial barrier, leading to a reduction in ZO-1, occludin, and claudin-1 expression.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 99%
“…8 PM deposits persist in close proximity to endothelial cells, where they can cause inflammation, immunological responses, and endothelial barrier failure. 9 Also it has been noticed that indoor air pollution may impact canine atopic dermatitis. 2100, assuming medium-fertility variant scenarios.…”
Section: Patients With Allergicmentioning
confidence: 99%
“…Low emission and congestion charging zones have been effective in reducing pollution‐related health outcomes 8 . PM deposits persist in close proximity to endothelial cells, where they can cause inflammation, immunological responses, and endothelial barrier failure 9 . Also it has been noticed that indoor air pollution may impact canine atopic dermatitis 10 …”
Section: Relevance Of the One Health Approach For Clinical Practice A...mentioning
confidence: 99%